Can Serial Measurement Enhance the Diagnostic Value of Procalcitonin as a Marker of Gram-negative Bacteremia in Children with Acute Leukemia? - Zümrüt Şahbudak Bal; Gülinaz Ercan; Deniz Yılmaz Karapınar (Galenos Yayinevi, 2019)
Aim:Despite improvements in diagnosis and treatment, infections are still major cause of morbidity and mortality in children with febrile neutropenia (FN). In these patients, due to inadequate inflammatory response and subtle clinical symptoms, to determine the source of infection can be challenging. Therefore, it is important to distinguish infections from other non-infectious causes, for both to choose appropriate antibiotic and to reduce the redundant antibiotic use.Materials and Methods:In this retrospective study, we aim to evaluate serial procalcitonin (PCT) levels for predicting bacteremia particularly caused by Gram-negative microorganism.Results:Among FN episodes caused by Gram-negative microorganism, the median level of second PCT sample obtained between 48 and 72 hours PCT 2 was found to be significantly higher when compared to infections caused by Coagulase-negative Staphylococcus or culture-negative confirmed infections, p value was 0.003; however, fever onset PCT 1 and C-reactive protein (CRP) 1 values showed no significant difference (p>0.05). The area under curve values demonstrated by receiver operating characteristic (ROC) analysis for CRP 1, CRP 2, PCT 1, PCT 2 were 0.664, 0.748, 0.504 and 0.842, respectively.Conclusion:This study showed that initial PCT levels were not significantly correlate with culture-confirmed bacterial infection. Therefore, initial PCT values do not help the clinicians in terms of administering or postponing empirical antibiotics at the time of fever onset. However, third day PCT levels present as a good diagnostic marker due to a higher sensitivity and specificity when comparing them to the initial values. Determination of serial PCT may enhance the diagnostic value of PCT diagnostic marker in FN episodes caused by Gram-negative bacteria with a high sensitivity (87.5%). This study also demonstrated that PCT could be used to rule out bacterial infections particularly caused by Gram-negative bacteria.